(untitled) (Global Journal of Science Frontier Research, 2012)
Cotton / Nylon blended fabrics are normally dyed by two-bath or one-bath two-step dyeing method. This paper deals with dyeing nylon/cotton blends to a solid shade in one bath using one dye. In this study, the fabric treated with chloroacetic acid (CAA), to form the anionic form followed by the cationization form using the inorganic salt of magnesium chloride. The effect of treatments on dyeability, fastness, and few physicochemical properties has been investigated, and results are presented. The dyed fabric featured excellent tone-in-tone effects and color fastness, and the process featured shortened time and saved cost.